Educational Management Strategies Amid the Development of Artificial Intelligence - Saipul Saipul; Suwarni Suwarni; Asnawati Asnawati; Mardiana Mardiana (Journal of Educational Studies, 2025)
The rapid development of artificial intelligence (AI) has altered the strategic landscape of educational management, yet many institutions still approach AI as a technical tool rather than as an organizational transformation issue. This study aims to examine how educational management strategies can be redesigned to balance data-driven decision-making, human-centered leadership, teacher capacity building, and ethical governance. Using an explanatory sequential mixed-methods design, the proposed study involved 286 school leaders, teachers, and administrative staff selected through stratified proportional sampling, followed by interviews with 18 key informants. Quantitative data were collected using validated Likert-scale instruments measuring AI strategic readiness, human-centered leadership, ethical governance, teacher AI literacy, and perceived management effectiveness. Data were analyzed using descriptive statistics, confirmatory factor analysis, multiple regression, and thematic coding. The illustrative findings indicate that human-centered leadership and ethical governance exert stronger effects on educational management effectiveness than AI infrastructure alone. AI strategic readiness contributes positively when mediated by teacher AI literacy and supported by transparent policy, professional learning communities, and accountable data governance. Contrary to established beliefs that technological adoption is the primary driver of AI-enabled educational improvement, this study argues that strategic value emerges when AI is institutionally embedded within participatory leadership and pedagogical judgment. The study fills the void by integrating socio-technical transformation theory and human-centered distributed leadership into a strategic framework for education management in the AI era. The implications emphasize the need for AI literacy programs, ethical protocols, evidence-informed planning, and adaptive leadership models that preserve human agency while improving organizational efficiency.